AUDIT QUALITY AS AN INTERVENING VARIABLE INFLUENCES THIN CAPITALIZATION ON TAX AVOIDANCE - Maharani, Destin Alfianika; Fitriana, Aning; Darmawan, Almas Rifqy (Riau International Conference on Economics, Business and Accounting, 2025)
Tax avoidance constitutes a violation of tax law through the exploitation of legal loopholes to evade tax responsibilities. In Indonesia, existing laws and regulations contain loopholes that enable taxpayers to evade taxes through various means, such as securing large loans from banks, offering in-kind benefits, providing grants, and utilizing PP Number 23 of 2018. This research investigates the impact of thin capitalization on tax avoidance, considering audit quality as an intervening variable. The methodology employed is path analysis, utilizing purposive sampling based on the following criteria: 1) Companies listed on the Indonesia Stock Exchange from 2021 to 2023, 2) Companies within the mining sector and coal sub-sector during the same period, and 3) Companies that provide comprehensive information relevant to the research data, including debt, capital, tax payments, profit and loss statements, and external auditors utilized. The study’s results demonstrate that thin capitalization directly and significantly influences tax avoidance, whereas audit quality does not impact tax avoidance, nor does thin capitalization affect audit quality. Audit quality does not mediate the relationship between thin capitalization and tax avoidance. The inclusion of audit quality variables demonstrates no significant impact on firms employing highly qualified auditors to reduce tax avoidance practices. This study has not definitively identified the factors contributing to tax avoidance, as evidenced by the low R-squared value.